Molecular Docking Study of Gingkgo biloba Compounds as Potential Inhibitors of SARS-CoV-2 - Afladhanti, Putri Mahirah; Romadhan, Muhammad Despriansyah; Hamzah, Haidar Ali; Putri, Safa Nabila; Angelica, Ellen Callista (SCRIPTA SCORE Scientific Medical Journal, 2022)
COVID-19 pandemic caused by SARS-CoV-2 is a challenge for researchers to find effective drugs for this disease. Previous research had identified the role of Mpro, TMPRSS2, RdRp, and ACE2 which were useful as promising drug targets to inhibit SARS-CoV-2. This study aims to identify the potential compounds derived from Ginkgo biloba as potential SARS-CoV-2 inhibitors using a molecular docking study. A total of twenty-one compounds of Ginkgo biloba and comparative drugs were used in this study. The materials were downloaded from rcsb for protein targets and pubchem for comparative drugs and compounds. In this study, Lipinski rule of five using Swiss ADME web tool was used. Moreover, toxicity analysis using admetSAR 2.0 online test also used to predict toxicological profile of compounds. Dockings were carried out on Mpro, TMPRSS2, RdRp, and ACE2 protein targets by AutodockTools 1.5.6 and Autodock Vina. The visualization of molecular interaction was carried out by Discovery Studio v16. Nine compounds met the criteria as drug-like components and were safe. Docking results showed that ginkgolide-C and bilobetin showed strong molecular interactions to all protein targets compared to the comparative drugs and other compounds. In RdRp, ginkgolide-C showed the highest binding energy with -12.7 kcal/mol. Moreover, in TMPRSS2, ACE2 and Mpro, bilobetin also showed the highest binding energy with -12.7, -9.7 and -10 kcal/mol, respectively. Ginkgolide-C and bilobetin have the potential to be developed as SARS-CoV-2 inhibitors. Therefore, in vitro and in vivo investigations are needed to bring these compounds to the clinical setting.